2011
DOI: 10.1007/s12032-011-9872-5
|View full text |Cite
|
Sign up to set email alerts
|

IGHV gene rearrangements as outcome predictors for CLL patients: experience of Ukrainian group

Abstract: Important characteristics of chronic lymphocytic leukaemia (CLL) cells are biased immunoglobulin variable heavy chain (IGHV) gene repertoire and expression of stereotyped B-cell receptors (BCRs); however, their prognostic value (in contrast to the impact of IGHV gene mutational status) is less clear. To evaluate the impact of separate IGHV gene usage and expression of stereotyped BCRs in CLL prognosis. Clinical data and IGHV gene configuration were analysed in 319 consecutive patients with CLL. We found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
5
1
1
Order By: Relevance
“…Studies from Asia [21, 22], South America [23], and Europe [12, 26] showed a low representation of IGHV3-11 subfamily, with a similar proportion of M-CLL and U-CLL in this subgroup. However, the Ukrainian group showed that its presence was associated with an increased risk of developing autoimmune hemolytic anemia [25]. Interestingly, in our cohort, IGHV3-11 gene was significantly overused in the unmutated group and was associated with a lower OS ( P = 0.025), but we failed to find a relationship with the risk of developing autoimmune hemolytic anemia.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Studies from Asia [21, 22], South America [23], and Europe [12, 26] showed a low representation of IGHV3-11 subfamily, with a similar proportion of M-CLL and U-CLL in this subgroup. However, the Ukrainian group showed that its presence was associated with an increased risk of developing autoimmune hemolytic anemia [25]. Interestingly, in our cohort, IGHV3-11 gene was significantly overused in the unmutated group and was associated with a lower OS ( P = 0.025), but we failed to find a relationship with the risk of developing autoimmune hemolytic anemia.…”
Section: Discussioncontrasting
confidence: 64%
“…The higher usage of IGHV1-69 has been reported in Ukrainian [25] and Mediterranean [12] CLL patients. In accordance with these observations, IGHV1-69 was also the most frequently used segment of IGHV1 family in our studied population and the second most commonly detected in the global series (21 cases, 9.4%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Higher frequencies (89.3%) of unmutated immunoglobulin variable heavy chain (IGHV) genes were shown among 28 cleanup workers from 1986 with CLL, in comparison with 68.1% in 238 nonexposed CLL patients. In a later study, the same group of investigators failed to demonstrate any difference [40]. Comparison of genome changes in general exposed population vs. nonexposed one in the post-Chornobyl period describes upregulation of MYC , HNF1A , and HNF4A and YWHAG , NF-κB1, and SP1 , together with a downregulation of CEBPA , YWHAG , SATB1 , and RB1 [41].…”
Section: Discussionmentioning
confidence: 99%
“…Частота использования гена IGHV3-21 составила 7,7 % (n = 14), что примерно соответствует частоте, выявленной в популяции пациентов из Украины (5,8 %) [16]. В то же время это меньше, чем в сканди-навской когорте (11,7 %), и больше, чем в американ-ской (2,6 %) и средиземноморской (2,9 %) популяциях [17,18].…”
Section: результаты соотношение пациентов с мутированным и немутироваunclassified